KAJIAN LANDASAN HUKUM TERKAIT TUGAS POKOK DAN FUNGSI APOTEKER SEBAGAI PELAKSANA PENGADAAN PERBEKALAN FARMASI DI RUMAH SAKIT - Limba, Kristina Megi (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2020)
Management of pharmaceutical supplies is one of the pharmaceutical services in Hospital Pharmacy Installations. In the management process, the procurement stage greatly affects the availability of drugs and the hospital economy. Guaranteed product and sufficient amount of medicine is one of the most important aspects of a hospital to be able to provide the best service. This study aims to discuss the legal basics regarding the main duties and functions of pharmacists in drug management, particularly the procurement of pharmaceutical supplies in hospitals. This research uses descriptive analysis method. Literature used in the form of scientific journals and regulations related to the management of pharmaceutical supplies at the procurement. The legal basis that regulates the procurement of pharmaceutical supplies is Permenkes RI No.72 Tahun 2016 Tentang Standar Pelayanan Kefarmasian di Rumah Sakit and several other supporting regulations. The results of the literature study were the management of pharmaceutical activities in the hospital at the stage of procurement of pharmaceutical supplies carried out by IFRS led by pharmacists. Management of pharmaceutical supplies in hospitals is carried out with a one-door system because it can simplify the process of supervising and controlling pharmaceutical supplies, according to the procurement objectives stated in the Permenkes RI No. 72 Tahun 2016.